Brazil : Technical Assistance Report-Strengthening Fiscal Responsibility at the Subnational Level. (IMF Staff Country Reports; Country Report ;, 2020)
The fiscal challenges of Brazil's states and municipalities can have a significant impact on the economy and the provision of core public services. The subnational governments (SNGs) account for a large share of public expenditures, including public investment. As such, their fiscal problems can hamper the economic recovery and the public finances of the federal government. In recent years, many states and municipalities have been struggling with high debt or severe liquidity pressures. Some have already defaulted on part of their debt and are running payment arrears (wages and suppliers). The federal government has already provided a substantial package of financial support through debt service relief.